Performance analysis of different friction models in the numerical simulation of the isothermal forging process - Santos, Thomas Gomes dos; Alba, Diego Rafael; Rosiak, André; Schaeffer, Lirio (International Journal of Advanced Engineering Research and Science, 2022)
Finite element analysis is a powerful tool for the design and optimization of mechanical forming processes. To achieve accurate results, a precise knowledge of the fundamental process parameters is required. In this context, this work analyzes the influence of several friction models in the numerical simulation of isothermal forging processes for a commercial aluminum alloy. Using the commercial software FORGE NxT 2.0, the friction models of, Tresca, Coulomb-Tresca and the Viscoplastico(Norton) friction model were considered and their results compared to forging experiments of an axisymmetric geometry. The objective is to evaluate which of these friction models is more appropriate to simulate the process. Hot forging experiments were performed and the most relevant numerical results for the process final geometry, consumed energy, forming strength and temperature were compared with the experimental results.